The Effectiveness of Teaching Vocabulary by Using Cartoon Film toward Vocabulary Mastery of EFL Students - Munir, Fathul (Journal of English Language Teaching and Linguistics, 2016)
This article investigates the suitable media to develop students’ vocabulary in elementary level is audio visual media especially cartoon film media, the problems of the study are: (1) How is the students’ score before using cartoon film media? (2) How is the students’ score after using cartoon film media? (3) How is the effectiveness of using cartoon film media on the students’ vocabulary mastery? This research conducts experimental design; the research design used by the researcher is pre-experimental design in the form of one–group pre–test and post– test. The instruments were used are pre–test, treatment, and the post–test. The analysis technique of data analysis used t–test statistical analysis. The use of cartoon film media will be significant if t count > t table. Data analysis shows that t count > t table (5,20 > 1,71), so H0 is rejected or Ha is accepted. Based on the research finding, the researchers conclude that (1) the students’ mastery on vocabulary before taught by using cartoon film media can be seen from the result of pre – test, there are 15 students get excellent result, there are 2 students get good result , there are 4 students get enough result , there are 3 students get less result and 1 student get low result . It means that there are 32% students who get low score. (2) The students’ mastery on vocabulary after taught by using cartoon film media can be seen from the result of post – test, there are 19 students get excellent result , there are 5 students get good result and there is 1 student get enough result . (3) The significant different, between students’ mastery on vocabulary before and after taught by using cartoon film media can be seen from the result of pre – test, it showed that 15 students who get score 80 – 100 where as the result of post – test showed that 19 students who get score 80 – 100. It means that the result of this research showed that t count > t table (5,20 > 1,71). It indicates that cartoon film is suitable to teach vocabulary. So from the result the researchers suggest to the English teacher that cartoon film is effective to teach vocabulary for young learners